Pilot randomized clinical trial targeting anxiety sensitivity: effects on physical activity. Issue 3 (4th May 2022) - Lanoye, Autumn; Rybarczyk, Bruce; Evans, Ronald; Leahey, Tricia; LaRose, Jessica
ABSTRACT: Anxiety sensitivity (AS)—the tendency to interpret anxiety as an aversive state—is associated with low rates of physical activity. Previous interventions targeting AS via exercise-based interoceptive exposure have not assessed physical activity as an outcome and are limited by brief follow-up periods. This study replicated and extended previous work by including a 6-week follow-up and assessing physical activity. Participants were 44 sedentary young adults with elevated AS randomized to intervention (six 20-minute sessions of moderate-intensity walking) or assessment-only control. Assessments of AS and physical activity were conducted at baseline and weeks 2 (post-treatment), 4, and 8. Between-group change in AS and physical activity over time was assessed using hierarchical linear modeling. The intervention condition demonstrated a marginally significant reduction in AS compared to control at week 4, which eroded by week 8. There were no significant between-group differences for change in physical activity. Findings indicate that a brief intervention might not be sufficient to produce lasting changes in AS or related exercise avoidance without additional treatment. Intervention effects were weaker than previous reports, which may be due to the greater racial/ethnic diversity of the current sample. Future research should objectively measure physical activity and explore individual variability in response.ClinicalTrials.gov identifier: NCT03128437